THE INFLUENCE OF TOTAL QUALITY MANAGEMENT ON GOOD GOVERNANCE THROUGH COMMITMENT ORGANIZATIONAL OF STATE SENIOR HIGH SCHOOL AND VOCATIONAL SCHOOL IN SURABAYA - Sigit Priyo Sembodo (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2016)
This study aims to analyze the influence of the Total Quality Management to Good Governance through the organizational Commitment. There are six elements on Total Quality Management, which are Leadership, Education and Training, Support Structure, Efective Communication, Reward and Performance Measurement especially in state senior high school and vocational school in the city of Surabaya. To achieve those objectives the survey was conducted by collecting data with the instrument of questionnaires, the data were analyzed by using Structural Equation Modeling with using Amos software version 21 in order to test a model that has been collated in a framework based on the theory and empirical studies. The results showed that (1) the Total quality management is implemented by educational institutions through Leadership, Training, Support Structure, Communication, Reward and Performance Measurement. The improvement of each element in an total quality management may affect to the implementation of good governance in educational institutions in the city of Surabaya through organizational commitment, unless the elements of leadership and training did not affect significantly to the implementation of Good Governance or which have legal certainty, responsive, open, manage budgets, accountable, effective, efficient and ethical. Implementation of Good Governance can be embodied either by increasing the commitment of government actors in this case were the perpetrators of education that will create public service in the field of education in accordance with desired by the community. (2) Management Model of integrated quality in state senior high school and vocational school need to realize some of the necessary elements are Leadership, Training, Structural Support, Communications, Choice and Performance Measurement for the elements of the educational institutions can support the implementation of good governance. Although the organizational commitment also affects directly or indirectly to the good governance in accordance with the principles of Good Governance.Keywords:Leadership, Training, Support Structure, Communication, Award, Performance measurement, organizational commitment and Good Governance.